IMPLEMENTATION OF FINANCIAL REPORTS BASED ON PSAK 45 - Afifah; Haliah; Nirwana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Objective: This research aims to analyze the implementation or application of the annual financial reports of non-profit organizations based on Statement of Financial Accounting Standards 45. Methodology: This research uses qualitative descriptive with sampling related to annual financial report data ending 31 December 2022 at the office Dompet Dhuafa Foundation using data collection techniques through documentation and interviews with informants as supporting material. The data analysis used is descriptive by analyzing it to draw conclusions. Results: The results of this research indicate that the Dompet Dhuafa has complied with the PSAK 45 by paying attention to each component contained in the statement. Limitations: This research cannot update the period or year of annual financial report data as research data, and the research object only focuses on one object, as well as narrow variables. Contribution: This research are expected to broaden the knowledge horizons of readers, especially for future researchers who wish to research related to the research focus raised, in this case regarding the financial reports of non-profit organizations based on PSAK 45 as part of public sector accounting science. Practical Implications: This research are certainly expected for companies, especially those operating in the field of non-profit organizations, so that through this research company management can take careful suggestions or considerations regarding PSAK 45 in the process of presenting their financial reports. Novelty: Referring to the researcher's point of view, the novelty of this research is that it obtain result in accordance with existing theory.